Prevalence and associated factors for stunting among 6-12 years old school age children from rural community of Humbo district, Southern Ethiopia - Tesfahun Yonas Bogale; Elazar Tadesse Bala; Minyahil Tadesse; Benedict Oppong Asamoah (BMC, 2018)
Abstract Background Stunting is one of the most serious and challenging public health problems in Ethiopia, which constitute a significant obstacle to achieving better child health outcomes. This study aimed to assess the prevalence and factors associated with stunting among 6-12 years old children in Humbo district, Southern Ethiopia. Methods This was a cross-sectional study conducted among 633 children 6-12 years old living in Humbo district, Southern Ethiopia, from March to April, 2015. A multistage cluster sampling technique was used to select participants from households in eight Villages in the study area. Height was measured using standard methods and height for age Z-score was computed to assess stunting. EPI info version 3.5.4 was used for data entry, whereas Anthroplus software and SPSS version 20.0 were used for computation of height for age Z-scores and statistical analyses respectively. Simple and multiple logistic regression analyses were used to examine factors associated with stunting in the study sample, using 95% confidence limits (statistical significance set at p < 0.050). Results Prevalence of stunting was 57%, about, 3.5% were severely stunted, 27.3% moderately stunted and 26.4% mildly stunted, and the mean (SD) was − 1.1 (±1.2). About 7 (1.1%) boys and 15 (2.4%) girls were severely stunted. Age groups 10-12 years had significantly higher rate of stunting than others. Age (AOR = 1.7, 95% CI = 1.1-2.6), big family size (AOR = 4.6, 95% CI = 2.2-9.5) and field disposal of wastes (AOR = 2.7, 95% CI = 1.2-5.8) were factors significantly associated with stunting. Conclusion This study exposed high rate of stunting among school age children. Stunting remains a noticeable attribute of rural school age children. Findings suggest the need to implement evidence-based school-aged rural children nutrition policy and strategies as well as need for intervention to improve domestic waste management system in the rural community.